Serum glial fibrillary protein reflects early brain injury dynamics and cognitive changes after deep brain stimulation surgery - Anika Frank; Jonas Arjomand; Jonas Bendig; Mia Delfs; Lisa Klingelhoefer; Witold H. Polanski; Katja Akgün; Tjalf Ziemssen; Björn Falkenburger; Nils Schnalke (Scientific Reports)
Abstract Deep brain stimulation (DBS) is an efficient treatment for movement disorders, most commonly Parkinson’s Disease (PD), dystonia and essential tremor. DBS surgery carries risks, e.g. the risk of delayed peri-lead edema (PLE) and the risk of postoperative cognitive decline. The mechanisms of these complications are not fully understood and there is no established biomarker to screen for these complications after DBS surgery. To explore the diagnostic value of two blood-based markers representative for distinct types of brain injury, we characterized the dynamics of serum glial fibrillary acidic protein (sGFAP, for glial injury) and serum neurofilament light chain (sNfL, for neuronal-axonal injury) following DBS surgery. We analyzed longitudinal dynamics of serum protein levels in 58 patients undergoing deep brain stimulation (DBS) at our center for half a year post-surgery. Serum GFAP responded much more rapidly after brain surgery, returning to baseline after weeks, whereas sNfL only returned to baseline after months. Patients with lower preoperative cognitive performance exhibited higher postoperative sGFAP levels, with sGFAP showing a stronger association with preoperative patient characteristics compared to sNfL. Further studies with long-term clinical follow-up are needed to fully evaluate the utility of sGFAP as a biomarker for both early and delayed complications after DBS surgery, including cognitive decline and potential foreign body reactions to the implanted lead.